Web-Based Level Crossing Control System Monitoring Device (Software) - Mehta, Rahul; Wasudarae Khond, Viveko (Nusantara Publisher, 2024)
Failure function of level crossing control starts from not fulfillied the technical specifications in the level crossing operation. So it is necessary to have a monitoring system for the control of a level crossing door. This research was conducted at the level crossing of the Indonesian Railway Academy. The device circuit is arranged by attaching the sensor to the battery input, and inputing the flashing unit. Installation of sensors on the battery input is intended so that when the supply of voltage and current entering the battery does not meet specifications, it will be known that the charger battery is in trouble. Installation of sensors at the flashing input unit is intended so that when the supply of voltage and current entering the flashing unit is not according to specifications, it will be known that the supplier has a problem. The sensor will be connected to Arduino Mega which will then be sent to the database. From the data database the voltage and current will be processed in the web and displayed. If the voltage and current data from the database do not match specifications, a notification will appear on the web. Afterthat, it can be repaired by a technician.